Kariera zawodowa generacji X i Y - perspektywy rozwoju na tle tendencji do uelastyczniania pracy - Rutkowska, Monika (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Several external factors have come together over the past decade to impact the nature of world of work and organizations. These factors raise important challenges for the career management and the way of career thinking; especially among young people. In this paper the author presents a short characteristic of generation X and Y and tries to explore how changes in employment affect the world of post-corporate careers. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 324-331